Responses of milk quality to roasted soybeans, calcium soap and organic mineral supplementation in dairy cattle diets - Adawiah .; Toha Sutardi; Toto Toharmat; Wasmen Manalu; Nahrowi . (Jurnal Ilmu Ternak dan Veteriner, 2006)
Milk quality is affected by feed nutrient either macronutrient or micronutrient.  Roasted soayabeans and calcium soap were to increase supply by pas protein and fat to dairy cattle. Thus, organic mineral was to increase bioavailability of feed mineral to animal.  The objective of this study was to evaluate roasted soybean, mineral soap and organic mineral supplementation on milk quality of dairy cattle.  Twenty lactating Frisian Holstein cows (initial weight 361.4 ± 40.39 kg) were assigned into a randomized complete block design with 5 treatments and 4 blocks. The treatments were A: basal diet, B: A + roasted soybean, C: B + calcium soap of corn oil, D: C + calcium soap of corn oil, E: C + calcium soap of fish oil. The experimental diets were offered for 9 and 2 weeks preliminary. The results of the experiment showed that milk protein and lactose were not affected by diets.  Milk dry matter  of cows fed A, B, and D diets were higher (P<0.05) than those of fed C and E diets.  Milk fat of cows fed A,  B and D diets were higher (P<0.05) than those of  fed C and E diets. Milk density of cows fed B and E diets were higher (p<0.05) than those of fed A, C and D diets. Milk TPC of cows fed B diet were higher (0.05) than those of fed A, C, D, and E diets. It is concluded that milk quality especially milk protein and lactose concentration are not affected by roasted soyabeans, Ca-soap, and organic mineral. Calcium soap of fish oil and organic mineral decrease population of milk bacteria. Key Words: Calcium Soap, Organic Mineral, Roasted Soyabeans, Dairy Cattle, Quality Milk